2023
DOI: 10.1038/s41408-023-00922-7
|View full text |Cite
|
Sign up to set email alerts
|

U2AF1 pathogenic variants in myeloid neoplasms and precursor states: distribution of co-mutations and prognostic heterogeneity

Talha Badar,
Yenny A. Moreno Vanegas,
Ahmad Nanaa
et al.

Abstract: We have previously recognized the genotypic and prognostic heterogeneity of U2AF1 mutations (MT) in myelofibrosis (MF) and myelodysplastic syndromes (MDS). In the current study, we considered 179 U2AF1-mutated patients with clonal cytopenia of undetermined significance (CCUS; n = 22), MDS (n = 108), MDS/acute myeloid leukemia (AML; n = 18) and AML (n = 31). U2AF1 variants included S34 (60%), Q157 (35%), and others (5%): corresponding mutational frequencies were 45%, 55%, and 0% in CCUS; 57%, 39%, and 4% in MDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Our observations of RAS pathway co-alterations ( CBL and KRAS ) in the EPI6 signature aligns with the documented activation of this pathway in CUX1 -altered MNs, as recently demonstrated in the context of 7q alterations in myeloid neoplasms [ 33 ]. Consistent with a previous study by Badar and coworkers which identified a significant association between TP53 mutations and the Q157 variant in U2AF1 -mutated MNs, our cohort also exhibited a marked predominance of the U2AF1 Q157 variant compared to the S34F variant [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our observations of RAS pathway co-alterations ( CBL and KRAS ) in the EPI6 signature aligns with the documented activation of this pathway in CUX1 -altered MNs, as recently demonstrated in the context of 7q alterations in myeloid neoplasms [ 33 ]. Consistent with a previous study by Badar and coworkers which identified a significant association between TP53 mutations and the Q157 variant in U2AF1 -mutated MNs, our cohort also exhibited a marked predominance of the U2AF1 Q157 variant compared to the S34F variant [ 34 ].…”
Section: Discussionsupporting
confidence: 92%